A interdisciplinaridade entre as ciências e a educação física na visão de alunos do ensino fundamental e médio - Weber, Jacir Vicente (2013)
The present study investigated the perspective of students from private and public schools about the existence of interdisciplinarity between the contents of Sciences and Physical Education. The subject of interdisciplinarity is understood as a way of conducting the classroom, in which a theme is proposed by approaches of different subjects. That is to comprehend, to understand the parts that connect different areas of knowledge in order to bring something innovative, to open wisdoms, recover possibilities and overcome the fragmented thinking. The research subjects included 1830 students from junior high (6th, 7th and 8th grades) and high school (1st, 2nd and 3rd grades in the Brazilian educational system), of which 1030 were from public schools and 800 studied in private schools in the city of Santa Maria (RS Brazil), aged between 10 and 18 years old. The subjects answered to the following question: Do you believe that there is a relation between Sciences and Physical Education? Yes or no and justify your answer. The research results are presented as 2 articles e 1 manuscript. Among the several results obtained we can highlight as the most relevant Article 1, in which 33% of junior high and 38% of high school students possess the perception that the subjects of Physical Education and Sciences are connected. Manuscript 2 reveals that 77,9% to 79,2% of high school students realize there is an interdisciplinary relation between the knowledge from Sciences and Physical Education. Whilst in Article 3, when analyzing the results obtained, 74,6% of high school students from public school and 59,2% from private schools did not find any interdisciplinary relation between Sciences and Physical Education in their school. As final conclusion we detected that in both private and public schools, whether the students were from junior high or high school, they have the opinion that there is an interdisciplinary relation between these knowledges.